Parent Diet Quality and Energy Intake Are Related to Child Diet Quality and Energy Intake - Robson, Shannon M. (J Acad Nutr Diet, 2016)
BACKGROUND: Parents' diets are believed to influence their children's diets. Previous studies have not adequately and simultaneously assessed the relation of parent and child total diet quality and energy intake. OBJECTIVE: To investigate if parent and child diet quality and energy intakes are related. DESIGN: A cross-sectional analysis using baseline dietary intake data from the Neighborhood Impact on Kids (NIK) study collected in 2007-2009. PARTICIPANTS/SETTING: Parents and 6-12 year old children from households in King County (Seattle area), WA and San Diego County, CA, targeted by NIK were recruited. Eligible parent-child dyads (n=698) with two or three 24-hour dietary recalls were included in this secondary analysis. MAIN OUTCOME MEASURES: Child diet quality (Healthy Eating Index-2010 [HEI-2010], Dietary Approaches to Stop Hypertension [DASH] score, and energy density (for food-only) and energy intake were derived from the dietary recalls using Nutrition Data Systems for Research. STATISTICAL ANALYSES PERFORMED: Multiple linear regression models examined the relationship between parent diet quality and child diet quality, and the relationship between parent energy intake and child energy intake. In both analyses, we controlled for parent characteristics, child characteristics, household education and neighborhood type. RESULTS: Parent diet quality measures were significantly related to corresponding child diet quality measures: HEI-2010 (standardized beta [β] = 0.39, p<0.001); DASH score (β = 0.33, p<0.001); energy density (β = 0.32, p<0.001). Parent daily average energy intake (1763 ± 524 kilocalories) also was significantly related (β = 0.30, p<0.001) to child daily average energy intake (1751 ± 431 kilocalories). CONCLUSION: Parent and child intakes were closely related across various metrics of diet quality and for energy intake. Mechanisms of influence are likely to be shared food environments, shared meals, and parent modeling.